A multi-criteria decision making analysis for feasibility of nanoparticle addition in biohydrogen production enhancement for scaling-up studies - Yoruklu, Hulya Civelek; Filiz, Bilge Coskuner; Figen, Aysel Kanturk; Ozkaya, Bestami (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
Nanoparticles (NPs) thanks to their unique features such as large surface area, high catalytic activity and intra-cellular electron transfer ability used as an enhancement additive in biohydrogen production. Up to date, inorganic, organic and their mixtures of various NPs were produced from different input sources and synthesis methodology. The NPs properties and cost minimization are the critical factors for the scale up studies of industrial applications. Nevertheless, there have not been any study on the determination of the most efficient and feasible NPs in biohydrogen production for the scaling up the process. In this study, the NPs used for biohydrogen production enhancement over Clostridium sp. by dark fermentation were examined and these studies were evaluated to determine the most effective and feasible NPs using the two-stage TOPSIS method. As a result, iron-containing NPs (hematite, magnetite) were determined as the most effective and economical NPs for increasing the yield.& COPY; 2022 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Dark fermentation; Biohydrogen; Nanoparticles; TOPSIS; Scaling-up; Clostridium sp; FERMENTATIVE HYDROGEN-PRODUCTION; WASTE-WATER; ENTEROBACTER-CLOACAE; MIXED CULTURE; NICKEL; OPTIMIZATION; ENERGY; METAL; Chemistry; Electrochemistry; Energy & Fuels